Specialized clinical cytology may improve the results of EUS (endoscopic ultrasound)-guided fine-needle aspiration (FNA) from pancreatic tumors - Schneider, Arne R.; Nerlich, Andreas; Topalidis, Theodoros; Schepp, Wolfgang (Endoscopy International Open, 2015)
Background and study aims: A variety of factors (needle type, needle passes, tumor location, cytological assessment, etc.) may influence the diagnostic accuracy of endoscopic ultrasound-guided fine-needle aspiration cytology (EUS-FNAC) from pancreatic tumors. Whereas most published studies report a diagnostic accuracy of > 80 % for EUS-FNAC, the results in routine settings are often considerably lower. This retrospective study aimed to define the effect of switching microscopic assessment from a standard pathology department to a highly specialized institute of cytology.Patients and methods: A total of 63 patients underwent EUS-FNAC of solid or semisolid pancreatic masses. Specimens of the first consecutive 20 cases (Phase 1) were assessed by the local department of pathology. Then in Phase 2, involving another 43 subsequent cases, a specialized cytology laboratory examined all aspirates. All EUS-FNACs were performed in the same manner, using a 22-gauge needle. After cytological evaluation, all patients either underwent surgery or were followed up for at least 6 months.Results: Of the tumors, 56 were solid and 7 semisolid; the mean size was 30 mm. Sensitivity (sens.), specificity (spec.), positive predictive value (PPV), and negative predictive value (NPV) of EUS-FNAC were 38.5 % (95 %CI [confidence interval] 13.9 – 68.4 %), 100 % (59.0 – 100 %), 100 % (47.8 – 100 %), and 46.7 % (21.3 – 73.4 %) during Phase 1 versus 91.4 % (95 %CI 76.9 – 98.2 %), 100 % (63.1 – 100 %), 100 % (89.1 – 100 %), and 72.7 % (39.0 – 94.0 %) during Phase 2.Conclusion: These results emphasize the considerable impact of a dedicated cytological evaluation on the results of EUS-FNAC.